Occupational hearing loss: tonal audiometry X high frequencies audiometry - Lauris, José Roberto Pereira (International Archives of Otorhinolaryngology, 2009)
Introduction: Studies on the occupational exposure show that noise has been reaching a large part of the working population around the world, and NIHL (noise-induced hearing loss) is the second most frequent disease of the hearing system. Objective: To review the audiometry results of employees at the campus of the University of São Paulo, Bauru. Method: 40 audiometry results were analyzed between 2007 and 2008, whose ages comprised between 32 and 59 years, of both sexes and several professions: gardeners, maintenance technicians, drivers etc. The participants were divided into 2 groups: those with tonal thresholds within acceptable thresholds and those who presented auditory thresholds alterations, that is tonal thresholds below 25 dB (NA) in any frequency (Administrative Rule no. 19 of the Ministry of Labor 1998). In addition to the Conventional Audiologic Evaluation (250Hz to 8.000Hz) we also carried out High Frequencies Audiometry (9000Hz, 10000Hz, 11200Hz, 12500Hz, 14000Hz and 16000Hz). Results: According to the classification proposed by FIORINI (1994), 25.0% (N=10) they presented with NIHL suggestive audiometric configurations. The results of high frequencies Audiometry confirmed worse thresholds than those obtained in the conventional audiometry in the 2 groups evaluated. Conclusion: The use of high frequencies audiometry proved to be an important register as a hearing alteration early detection method.